CHARACTERIZATION OF MAJOR ALLERGENS OF MACROBRACHIUM ROSENBERGII (GIANT RIVER PRAWN) BY ALLERGENOMIC APPROACH AND THEIR THERMOSTABILITY PROPERTIES (Jurnal Teknologi (Sciences & Engineering), 2018)
Prawn allergy is a common cause of allergic reactions in countries where crustacean is a famous seafood. Macrobrachium rosenbergii (giant river prawn) is declared as a local major food allergens, causes severe symptoms like asthma and anaphylactic shock. Therefore, the goal concerning this research is to identify the allergenicity of heat treated of M. rosenbergii. Prawn extracts have been prepared using fresh raw prawn and three heat-treated prawn flesh (boiled, steamed, fried), then afterward analyzed by the usage of sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) in conformity with their protein profiles. Allergenic proteins were identified by means of immunoblotting by the use of sera from 30 prawn-allergic patients. The identities of selective major allergens were then determined by mass-spectrometry analysis. The raw prawn has 27 protein fractions between 6 to 207 kDa, while the heat-treated prawns have reduced number of protein bands. Six prominent bands at 72, 65, 48, 38, 36, and 30 kDa were considered as the major allergens of raw extract. Meanwhile, after heat remedies applied, most of the IgE-binding bands were disappeared except for three major allergens at 38, 36 or 30 kDa which were still remain to be seen, suggesting as highly thermostable allergens. Among heat-treated prawns, steamed and boiled elicited more allergenic bands, contrast to fried prawn extract. Mass spectrometry analysis identified two selected major allergens at 36 and 48 kDa as tropomyosin and arginine kinase, respectively. As a conclusion, this study indicated that both thermostable and thermolabile proteins from M. rosenbergii were allergenic. Tropomyosin and arginine kinase were identified as the most important major allergens. Thus, the knowledge on thermostability of prawn allergens are crucial for improving diagnosis and management of prawn allergic patients in this county.Â